1999
DOI: 10.1159/000028317
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of GABA-Mediated Contractions of Rat Isolated Ileum by Experimental Diabetes

Abstract: The effect of diabetes induced by pretreatment with streptozotocin 6 weeks prior to the study on the responses induced by γ-aminobutyric acid (GABA), the GABAA agonist 3-aminopropane sulfonic acid (3-APS), and acetylcholine in the rat isolated ileum was evaluated. GABA, 3-APS, and acetylcholine showed a rightward shift in their concentration-dependent effects in the ileum that also attained a lower maximum in streptozotocin-diabetic rats as compared with control rats (p < 0.05). It is suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Some studies have shown that GABA could decrease basal tone and phenylephrine-induced contraction in normal isolated aortic rings (Gimeno et al 1994), and GABA has a direct effect on vascular smooth muscle (Ozdem and Sadan 1999). Ozdem and co-workers have shown that besides the direct modulatory action that GABA exerts on normal vascular smooth muscle, it also modulates endothelial function (Ozdem 1997). In our previous study, we showed that GABA can induce endothelial vasorelaxation in control and diabetic groups and this effect was mediated by same pathway in both groups.…”
Section: Introductionmentioning
confidence: 63%
“…Some studies have shown that GABA could decrease basal tone and phenylephrine-induced contraction in normal isolated aortic rings (Gimeno et al 1994), and GABA has a direct effect on vascular smooth muscle (Ozdem and Sadan 1999). Ozdem and co-workers have shown that besides the direct modulatory action that GABA exerts on normal vascular smooth muscle, it also modulates endothelial function (Ozdem 1997). In our previous study, we showed that GABA can induce endothelial vasorelaxation in control and diabetic groups and this effect was mediated by same pathway in both groups.…”
Section: Introductionmentioning
confidence: 63%
“…In addition, the relaxations induced by GABA were not significantly changed in hyperhomocysteinemic duodenal tissues compared with control. The finding that relaxation responses to GABA, EFS, and ATP were not different between hyperhomocysteinemic and control rats suggests that hyperhomocysteinemia does not cause an important impairment on NANC innervation of the rat duodenum such as previously shown in diabetic models [34,57]. So possible gastrointestinal symptoms or gastroenteropaties that could be associated with hyperhomocysteinemia may be a result of other mechanisms.…”
Section: Discussionmentioning
confidence: 56%
“…8,14 Results suggest that GABA decreases the contractile responses of airway smooth muscles to cholinergic nerve stimulation by inhibiting the release of ACh from post-ganglionic parasympathetic nerves in the guinea-pig trachea. 26,27 It is also possible that the inhibitory effect of GABA and GABA analogues on contractions of tracheal smooth muscle is impaired in diabetes. 15 The GABA-producing enzyme glutamate decarboxylase (GAD) is a prominent auto-antigen in insulin-dependent diabetes mellitus (IDDM).…”
Section: Introductionmentioning
confidence: 99%
“…15,20,24,25 Recently, we have shown that induction of diabetes impairs the responsiveness of various smooth muscle tissues to GABA and its analogues in rats. 26,27 It is also possible that the inhibitory effect of GABA and GABA analogues on contractions of tracheal smooth muscle is impaired in diabetes. Thus, in the present study, we investigated the effect of GABA and selective GABA agonists and antagonists on neurally induced airway contractions in STZ-diabetic rats.…”
Section: Introductionmentioning
confidence: 99%